Analysis of Ecotourism Development from an Islamic Perspective - Firdaus Firdaus; Rafiuddin Rafiuddin; Hikmah Hikmah (JURNAL ECONOMINA, 2026)
This study examines the development of ecotourism from an Islamic perspective, focusing on the application of Islamic values, the various challenges that arise, and an ideal model relevant to the social and cultural context of Indonesia. This study employs a qualitative method using a literature review approach. The data sources include the Qur’an, authentic hadiths, classical fiqh literature, and national tourism policy documents. The results indicate that the development of ecotourism grounded in Islamic values has a solid theological foundation through the concepts of khalifah, amanah, and mizan. The application of Islamic values in ecotourism practices includes environmental conservation, community empowerment, the implementation of business ethics, and the provision of facilities that are welcoming to Muslim tourists. Nevertheless, the development of ecotourism based on Islamic values still faces various significant challenges, such as limited infrastructure, low public awareness, suboptimal regulations, and the dilemma between applying Islamic values and the principle of inclusivity. An ideal model for ecotourism development from an Islamic perspective must integrate the principles of maqasid al-shari’ah, the pentahelix collaboration approach, and the harmonization of Islamic values with local wisdom. Therefore, this study recommends strengthening Sharia-based regulations, enhancing community empowerment, and developing supporting infrastructure to realize sustainable Islamic ecotourism.